P129 Report of a respiratory health check in a self-selected group of male prisoners in Suffolk. (2nd December 2011) - Pearce, L J; Cecil, E; Phillips, C; Pulimood, T B; Laroche, C M
Abstract : Introduction: A health bus sponsored by Pfizer Ltd was loaned to Suffolk PCT for a 2-week period in June 2011, for the purpose of health promotion in a range of Suffolk locations. During this period, two prisons were visited, each on one occasion only. At each prison, the Unit Manager allowed prisoners to attend for voluntary health checks. As part of this assessment, members of the Suffolk COPD nursing team carried out a respiratory-focused questionnaire and spirometry on each volunteer. Method: Each prisoner was asked a series of specific questions concerning respiratory status, including past and present history of smoking tobacco and other substances, presence of current respiratory symptoms, history of known respiratory conditions and respiratory medications. The questionnaire was administered by a respiratory nurse consultant, while a trained respiratory nurse carried out spirometry. Results: 136 prisoners underwent the respiratory health check. Age range was 19–55 years, average 33 years, median 31 years. 90 (66%) were current smokers (13% of whom had started smoking in prison), and a further 35 (26%) were ex-smokers. 85 (79% of current smokers and 40% of ex-smokers) had also smoked cannabis. Conclusions: In 2008, smoking rates for England were reported to be around 21% of adults.1 This snapshot sample of two prisons in Suffolk is consistent with a higher prevalence of both current smoking (66%) and past smoking (26%) in prisoners, although the incidence may be artificially raised due to self selection for the health assessments. FEV1 /FVC ratio tended to be lower among smokers compared to ex smokers and never smokers. A more comprehensive study of prisoners should be considered, to reduce the burden of smoking related disease within the prison service.